Influence of company size, capital intensity, sales growth and profit management against tax avoidance - Rahayu, Cintia Febi; Mulyani, Nani (Educoretax, 2024)
This study aims to explore the influence of Company Size, Capital Intensity, Sales Growth, and Profit Management on Tax Avoidance in Consumer Non Cyclicals companies with food and beverage sub-sectors  listed on the Indonesia Stock Exchange during the 2018-2022 period. This study uses a quantitative approach with purposive sampling techniques, and involves 14 companies as a sample. The analysis method used is multiple regression with F test and T test using Eviews 12. The results show that Company Size has an effect on Tax Avoidance, while Capital Intensity, Sales Growth, and Profit Management have no effect on tax avoidance. However, simultaneously, all of these independent variables have a significant influence on Tax Avoidance. This research contributes to the Directorate General of Taxes in an effort to increase tax collection from companies, as well as provide insights for companies to comply with tax regulations and reduce tax avoidance practices. For the author, this study adds to the understanding of the variables that affect tax avoidance. Keywords: Company Size; Capital Intensity; Sales Growth; Profit Management; Tax Avoidance